Too late for Flor ; Greed for gold ; The new insecticides [videorecording] - Canlas, Ruben; Lazaro, Cheche (Quezon City Probe Productions, 1995)
Investigates the government's liability in the execution of Flor Contemplacion; the greed for gold that is dragging Philippine sports and the insects used as the safer and cheaper pesticide for the farmers.
Too late for Flor (15 min.) -- Greed for gold (13 min.) -- The new insecticides (10 min.).
VHS.
Credits : Reporter, Cheche Lazaro.
Keywords: Contemplacion, Flor; Philippines Sports Commission -- Corrupt practices; Insecticides -- Physiological effect; Sports -- Corrupt practices